Direct oxidation of alcohols to carboxylic acids using simple and economical Pd@Glu-HTC catalyst: practical and scalable approach towards biomass based value added chemicals - Kirdant, Swapnali P.; Bankar, Shubham R.; Jadhav, Vrushali H. (Biomass & Bioenergy, 2024)
Sustainable catalytic transformation of bio-based alcohols to high value-added fine chemicals is an important topic of research. This work described preparation of simple and economical Pd@Glu-HTC catalyst from biomass derived low cost D-glucose. Hydrothermal carbonization of glucose was carried out in first step to synthesize GluHTC support in a simpler, greener, economical and efficient manner followed by incorporation of palladium metal on surface of the catalyst in second step. The catalyst was characterized using techniques such as Fourier Transform Infrared Spectroscopy (FT-IR), Solid-state Cross-Polarization Magic Angle Spinning Carbon-13 (13C CPMAS), Energy-dispersive X-ray spectroscopy (EDAX), Powder X-ray diffraction (P-XRD), X-ray photoelectron spectroscopy (XPS), Thermogravimetric/Differential Thermal Analyzer (TG-DTA), Field emission scanning electron microscopy (FE-SEM) and High-resolution transmission electron microscopy (HR-TEM). The catalyst was evaluated for direct oxidation of alcohols to yield carboxylic acids and exhibited very good catalytic activity for wider substrate scope. Oxidation of alcohols was carried out using milder base, molecular oxygen and water as a solvent to achieve 92-99 % excellent yields. The practical utility of current strategy was also studied for gram scale synthesis of bio-based value added industrially important chemicals such as furoic acid (flavouring agent and preservative in industry), 2, 5-furan-dicarboxylic acid (monomer to 100 % fossil-free, recyclable polymer polyethylene furanoate (PEF), tetrahydro-2-furoic acid (production of many drugs) and vanillin (important product of flavor and fragrance industry). Pd@Glu-HTC catalyst was found to be reusable for four recycles and the catalytic performance was retained without any loss in its activity after four cycles.
Keywords: Bio-based chemicals; Carbonaceous catalyst; Carboxylic acid; Oxidation